2020
DOI: 10.1002/etc.4721
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal and Lethal Methods to Detect Recent Imidacloprid Exposure in Birds with Application to Field Studies

Abstract: We used domestic chickens (Gallus gallus domesticus) as a model for granivorous birds to identify methods to detect recent imidacloprid exposure in wild birds. We conducted dosing experiments of 1, 5, 10, and 20% of a reported median lethal dose for domestic chickens using repeated daily exposures over 7 d, at dosages equating to 1.04, 5.2, 10.4, and 20.8 mg/kg/d. We examined the parent compound and metabolites in serial collections of feces and blood during exposures and for 15 d after exposures. We also coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Since IMI has been reported to have multi-organ adverse effects, organ weights (liver, small intestine, colon, kidney, and spleen) were analyzed with respect to the body weights ( Table 1 ). The kidney and spleen were examined for toxicity as they are additional sites of IMI accumulation [ 31 , 32 ]. Kidney and spleen weights were unaltered, although Car −/− mice exposed to IMI had a decreasing trend compared to vehicle control ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since IMI has been reported to have multi-organ adverse effects, organ weights (liver, small intestine, colon, kidney, and spleen) were analyzed with respect to the body weights ( Table 1 ). The kidney and spleen were examined for toxicity as they are additional sites of IMI accumulation [ 31 , 32 ]. Kidney and spleen weights were unaltered, although Car −/− mice exposed to IMI had a decreasing trend compared to vehicle control ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[48][49][50][51] Previous studies have found that IMI is rapidly removed from the blood after exposure, but has higher residues in feces, brain, and liver. 52,53 The United States has stipulated that the maximum residue limit of IMI in poultry, fish, shellfish, and other foods is 0.05 mg/kg (http://www.tbtsps.cn). In our study, the results of HPLC-MS/MS confirmed the accumulation of IMI in quail liver tissue, which was much higher than the maximum residue limit of IMI in poultry in the United States, but Lut reduced the accumulation to a great extent.…”
Section: Discussionmentioning
confidence: 99%
“…IMI can enter the body through many ways to cause tissue injury, such as liver, kidney, brain, and muscle tissue 48–51 . Previous studies have found that IMI is rapidly removed from the blood after exposure, but has higher residues in feces, brain, and liver 52,53 . The United States has stipulated that the maximum residue limit of IMI in poultry, fish, shellfish, and other foods is 0.05 mg/kg (http://www.tbtsps.cn).…”
Section: Discussionmentioning
confidence: 99%